Progression types after antiangiogenic therapy are related to outcome in recurrent glioblastoma - Nowosielski, Martha; Wiestler, Benedikt; Goebel, Georg; Hutterer, Markus; Schlemmer, Heinz-Peter; Stockhammer, Günther; Wick, Wolfgang; Bendszus, Martin; Radbruch, Alexander (Neurology, 2014)
Objective: This retrospective study analyzed whether the type of radiologic progression, classified according to contrast enhancement on MRI T1-weighted sequences and changes in T2-hyperintense signal, is relevant for outcome in patients with progressive glioblastoma (pGB) treated with bevacizumab. - Methods: MRI scans of 83 patients with pGB treated with bevacizumab were evaluated prior to and at disease progression. Based on initial decrease in and subsequent flare-up of contrast enhancement in T1 and 2 patterns of T2-hyperintense tumor progression, progression types (PTs) were categorized as cT1 flare-up, T2-diffuse, T2-circumscribed, or primary nonresponder. Overall survival (OS), survival from start of bevacizumab therapy (OS_Bev), survival after bevacizumab failure (OS_PostBev), time from initial diagnosis until initiation of bevacizumab therapy (StartBevT), and time to bevacizumab progression were evaluated using Kaplan-Meier curves, log-rank test, and Cox regression analyses. - Results: The time observed for development of a T2-diffuse (n 5 15) or a cT1 flare-up (n 5 35) progression was longer than for progression in primary nonresponders (n 5 16) or T2-circumscribed progression (n 5 17). The T2-diffuse PT showed longer OS, OS_Bev, OS_PostBev, and StartBevT compared to the other PTs. Postprogression therapy tended to be relevant only for patients with a T2-circumscribed PT. - Conclusions: Radiologic PTs following bevacizumab treatment failure show differences in time to development and are related to outcome. We therefore hypothesize that these PTs reflect a different glioma biology, including differential resistance mechanisms to bevacizumab, and may be associated with different responses to postprogression therapy. Neurology® 2014;82:1684-1692
Gesehen am 23.09.2020